Трудовий договір як підстава виникнення трудових правовідносин - Якушев І.; Yakushev I. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
Стаття присвячена аналізу трудового договору як форми реалізації права на працю та підстави (юридичного факту) виникнення трудових правовідносин. Розглянуто особливості процедури укладення трудового договору та його оформлення залежно від трудової функції, яку буде виконувати працівник. Обґрунтовано висновок, що підставою виникнення трудових правовідносин є трудовий договір, незалежно від його форми і виду. Однією з обов’язкових умов трудового договору, без якої трудовий договір не може вважатися укладеним, є вказівка про трудову функцію працівника відповідно до Класифікатора професій. Оформлення трудового договору відбувається шляхом видачі наказу, у якому зазначається посада, на яку призначається працівник, або робота, яку він буде виконувати The article deals with the analysis of the employment contract as a form of realization of the right to work and the legal fact of labor legal relations emergence. Based on the analysis of the norms of the Labor Code of Ukraine, the author draws the conclusion about the need to distinguish between concluding the contract of employment and its execution. The conclusion of an employment contract may occur as a result of an agreement to perform some work, the actual admission of the employee to work, or it may imply the presence of the legal procedures (eg competitive selection, election for the position, etc.). The employment contract is executed by issuing an order or instruction on hiring or appointment to the position. The article substantiates that the basis of employment is an employment contract, regardless of its form (written or oral) and the type (contract, an employment contract for part-time work, an employment contract for temporary or seasonal work). One of the mandatory conditions of the contract of employment is an indication of the employee's job functions in accordance with the Classifier of Occupations. Without it the contract of employment cannot be considered as such that has been concluded. The employment contract is executed by issuing an order stating the position to which the employee is appointed or the work he will perform.
Contract of Employment as a Basis for labor Legal Relations
Keywords: право на працю; трудовий договір; трудові правовідносини; right to work; employment contract; labor relations